A CONCEPTUAL STUDY ON METHODOLOGIES FOR LANDSLIDE HAZARD: INVENTORIES, SUSCEPTIBILITY, VULNERABILITY, AND RISK ANALYSIS - Taye, Amar Jyoti; Tamang, Rubi (International Journal of Research -GRANTHAALAYAH, 2025)
Landslides pose a significant geohazard globally, particularly in Asia, which accounts for nearly 75% of worldwide landslide-related fatalities. The regions under the Himalayan Arc in India are especially vulnerable due to complex geomorphological, climatic, and anthropogenic factors. This conceptual review synthesizes existing methodologies for landslide hazard mapping by exploring four key dimensions: inventories, susceptibility, vulnerability, and risk assessment. The study highlights the importance of landslide inventories which serve as the foundation for accurate susceptibility modelling. Various susceptibility mapping approaches—qualitative, semi-quantitative, and quantitative have been reviewed. Further, vulnerability assessments through multidimensional frameworks, including heuristic and index-based methods, fragility curves, and numerical modelling, which evaluate the impact on both human and structural assets, are discussed. Finally, risk analysis is also deliberated through qualitative and quantitative lenses, integrating hazard intensity, vulnerability, and value of elements at risk. This review highlights the need for a multidisciplinary and mixed-method approach to enhance the accuracy, reliability, and practical applicability of landslide hazard assessments, particularly in data-scarce and high-risk regions.